2016
DOI: 10.3892/etm.2016.3225
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between recurrent gliomas and radiation necrosis using arterial spin labeling perfusion imaging

Abstract: Arterial spin labeling (ASL) magnetic resonance (MR) perfusion imaging has been proposed as an effective method to measure brain tumor perfusion. The aim of the present study was to evaluate the utility of this technique in the differentiation of recurrent gliomas from radiation necrosis. Twenty-one patients with surgically treated primary gliomas, including 16 cases of recurrent glioma and 5 of radiation necrosis were examined using 3.0T MR imaging (MRI). ASL and dynamic susceptibility contrast-weighted (DSC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 25 publications
(26 reference statements)
2
34
0
Order By: Relevance
“…The results are in good agreement with traditional perfusion imaging, and the combination with conventional MR images is widely used in the diagnosis and differential diagnosis of cranio-cerebral diseases [13,15,40]. In cases of glioma recurrence, the normalized ASL-CBF ratio was 74.83% higher than that of radiation-induced brain injury [41]. Current research on gliomas shows that ASL can be used to evaluate tumor microcirculation perfusion.…”
Section: Discussionsupporting
confidence: 71%
“…The results are in good agreement with traditional perfusion imaging, and the combination with conventional MR images is widely used in the diagnosis and differential diagnosis of cranio-cerebral diseases [13,15,40]. In cases of glioma recurrence, the normalized ASL-CBF ratio was 74.83% higher than that of radiation-induced brain injury [41]. Current research on gliomas shows that ASL can be used to evaluate tumor microcirculation perfusion.…”
Section: Discussionsupporting
confidence: 71%
“…Both conventional (including T 1 ‐ and T 2 ‐weighted images) and advanced sequences, including dynamic contrast imaging (DCE), diffusion‐weighted imaging (DWI), and arterial spinal labeling (ASL) have been applied to preoperatively classify glioma. Although it is generally reported that advanced sequences are superior to conventional ones in classifying glioma grades, controversies still exist about the diagnostic accuracy of MRI . The major reason is that only a small number of MRI attributes from the limited MRI modalities were utilized, leaving a huge amount of valuable multimodal image information unused, not to mention reflecting the heterogeneity of gliomas.…”
mentioning
confidence: 99%
“…MRI is a commonly used noninvasive technique for glioma diagnosis. Both conventional (including T 1and T 2 -weighted images) 4 and advanced sequences, including dynamic contrast imaging (DCE), diffusion-weighted imaging (DWI), 5,6 and arterial spinal labeling (ASL) 7 have been applied to preoperatively classify glioma. Although it is generally reported that advanced sequences are superior to conventional ones in classifying glioma grades, controversies still exist about the diagnostic accuracy of MRI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudoprogression is diagnosed when a post-radiation MRI indicates an increase in contrast enhancement that subsides with time, without any change in therapy, and may therefore have represented radiation change [1, 29]. However, pseudoprogression has also shown decreased perfusion on ASL in previous studies [10, 11] and its possible confounding effect of pseudoprogression is unlikely to have caused the association between decreased perfusion and shorter TTP in our current study.…”
Section: Discussionmentioning
confidence: 57%